Adolescent criminal behavior, population heterogeneity, and cumulative disadvantage: untangling the relationship between adolescent delinquency and negative outcomes in emerging adulthood - Makarios, Matthew D. (Crime & delinquency, 2017)
Developmentalists suggest that adolescent criminal involvement encourages later life failure in the social domains of education, welfare, and risky sexual activities. Although prior research supports a link between crime and later life failure, relatively little research has sought to explain why this relationship exists. This research attempts to understand why crime leads to negative social outcomes by testing hypotheses derived from the perspectives of population heterogeneity and cumulative disadvantage. Using data from the National Longitudinal Survey of Youth 1997, the results reveal that net of control variables and measures of population heterogeneity, adolescent criminal behavior consistently predicts school failure, being on welfare, and risky sexual activities. The findings also suggest that after controlling for delinquency, adolescent arrest negatively affects these factors. Furthermore, stable criminal traits and adolescent delinquency interact when predicting measures of poor social adjustment in early adulthood.